2016
DOI: 10.1007/s10344-016-1037-6
|View full text |Cite
|
Sign up to set email alerts
|

Does the blood-sucking nematode Ashworthius sidemi (Trichostrongylidae) cause deterioration of blood parameters in European bison (Bison bonasus)?

Abstract: European bison (Bison bonasus), after extinction in the wild at the beginning of twentieth century, were reintroduced in over 30 free-ranging populations in central and eastern Europe. Major threats to this species include disease and parasites. In the last decades, the highly pathogenic bloodsucking nematode Ashworthius sidemi (Trichostrongylidae) has been found in high infection intensity and prevalence within the abomasa of free-living European bison. We investigated the impact of this invasion on blood par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
(20 reference statements)
1
18
0
1
Order By: Relevance
“…Moreover, the histopathological examination of tissue from infected bison showed infiltrations of inflammatory cells in the walls of the abomasa and duodena (mainly lymphoid cells and eosinophils, as well as hyperaemia, oedema and lesions of mucosa and proliferation of lymphatic follicles) at various levels of intensity ( Osińska et al., 2010 ). Such serious histopathological lesions connected with a deterioration in blood parameters in infected animals ( Kołodziej-Sobocińska et al., 2016b ) confirm the parasite potentially has a strong impact on the bison population.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, the histopathological examination of tissue from infected bison showed infiltrations of inflammatory cells in the walls of the abomasa and duodena (mainly lymphoid cells and eosinophils, as well as hyperaemia, oedema and lesions of mucosa and proliferation of lymphatic follicles) at various levels of intensity ( Osińska et al., 2010 ). Such serious histopathological lesions connected with a deterioration in blood parameters in infected animals ( Kołodziej-Sobocińska et al., 2016b ) confirm the parasite potentially has a strong impact on the bison population.…”
Section: Discussionmentioning
confidence: 92%
“…Blood-sucking parasites, such as A. sidemi , are strongly pathogenic ( Osińska et al., 2010 ), especially as a cause of anaemia ( Stefański, 1968 , Gatongi et al., 1998 ). A study by Boughton and Hardy (1935) revealed that 2000 H. contortus females can suck 30 ml of blood per day; thus the high infection intensity of A. sidemi (reaching 44,300 nematodes) observed in bison in BPF may cause significant blood loss resulting in a serious impact on host condition ( Kołodziej-Sobocińska et al., 2016b ). Moreover, the histopathological examination of tissue from infected bison showed infiltrations of inflammatory cells in the walls of the abomasa and duodena (mainly lymphoid cells and eosinophils, as well as hyperaemia, oedema and lesions of mucosa and proliferation of lymphatic follicles) at various levels of intensity ( Osińska et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Po raz pierwszy w Polsce A. sidemi został wykryty w 1997 r. w Bieszczadach u wszystkich badanych tam żubrów, jeleni i saren (13)(14)(15) Przy użyciu badań histopatologicznych stwierdzono w przewodzie pokarmowym zarażonych żubrów rozległe zmiany zapalne, martwicze i zanikowe, które były najsilniej wyrażone u cieląt przy wysokiej intensywności inwazji (27). Wykazano również wpływ pasożyta na znaczne obniżenie parametrów hematologicznych ukła-du czerwonokrwinkowego (22). W wyniku tych badań można uznać nicienie A. sidemi za najbardziej patogenne pasożyty żubrów.…”
Section: Canadensis I E Alabamensis)unclassified
“…This indicates high susceptibility of captive-bred and immunologically naïve individuals to parasitological infection (Cunningham 1996). A high infection level of A. sidemi leads to deterioration of red blood cell parameters, which may weaken bison and increase their susceptibility to other pathogens (Kołodziej-Sobocińska et al 2016b). As many natural populations tend to be held in long-term balance by host–pathogen interactions (May 1988), acquisition of immunity to some diseases may require long-term and low-intensity exposure to pathogens (Wakelin 1978).…”
mentioning
confidence: 99%
“…It has been proposed that when there are parasites present in wild populations to which captive animals have not been exposed, then it may be advisable to provide low-level exposure in captivity to develop some immunity (Viggers et al 1993). Recently, since 2012, low A. sidemi infection intensity has been reported in captive bison (Kołodziej-Sobocińska et al 2016b; Krzysiak et al 2015). Hopefully, controlled exposure of animals to parasites prior to release may be beneficial and increase their immunity.…”
mentioning
confidence: 99%